Investigating the effect of the orientation program on the performance of academic advisor - Fatemeh Abbaszadeh; Mahboobeh Kafaei- Atrian; Saeideh Nasiri; Forough Faroughi (BMC Medical Education)
Abstract Background Teacher-student interactions and academic advisors are critical for student success and have positive effects on academic integrity. On the other hand, studies show that the performance of the academic advisors has not been able to gain the satisfaction of the students. Therefore, this study was conducted to investigate the effect of the orientation program on the performance of academic advisors from the perspective of students and advisor professors. Materials and methods This quasi-experimental study was conducted, before and after the intervention in 2022–2023 in Kashan School of Nursing and Midwifery. Data were collected from 220 students of different fields who were selected through stratified random sampling and 20 faculty advisors through a questionnaire of individual characteristics and two questionnaires “Evaluation of the academic advisor performance from the perspective of himself and the perspective of the student”. The intervention of this research included five 30 to 40-minute training sessions as a group for academic advisors. Data were analyzed using descriptive statistics (mean, standard deviation) and analytical statistics (repeated-measures ANOVA) via SPSS version 22 software. Results The results of the repeated-measures ANOVA showed that the mean score of advisor performance from the perspective of students was 88.31 ± 46.70 before the intervention, which reached 114.09 ± 45.79 and 99.76 ± 37.53, respectively, 6 and 12 weeks after the implementation of the orientation program. Also, the mean score of advisor performance from their perspective before the intervention was 118.13 ± 35.89 before the intervention, and 6 and 12 weeks after the implementation of the orientation program, it reached 160.38 ± 17.23 and 168.75 ± 8.10, respectively. Also, the results showed that the effect of time on the changes in the performance scores of the academic advisors was significant, which means that the performance scores of the academic advisors increased significantly(p < 0.05). Conclusions Considering the position of academic advisors and the effects of their performance on students, it is better to look at counseling as a subject that needs education in order to increase the ability of professors to provide counseling and also to improve the provision of services.